COMFORT LEVEL OF POST GRADUATE RESIDENTS WORKING IN DIFFERENT CLINICAL DOMAINS IN MANAGING COMMON OPHTHALMIC CONDITIONS - Jaffar, Sulman; Tayyab, Ali; Shah, Syed Shoaib; Naseem, Sajida; Ghazanfar, Haider (Journal of Ayub Medical College Abbottabad, 2016)
Background: Ophthalmological conditions are frequently encountered in almost all clinical specialties. Assessing the adequacy of ophthalmology teaching in undergraduate medical education is important in order to diagnose and manage different ophthalmological conditions. The objective of this study was to to determine the comfort level of post graduate residents working in different clinical domains in managing common ophthalmic conditions. Methods: A cross sectional survey involving 277 post graduate residents was carried out over a period of six months from June to December 2013 in both private and public tertiary care hospital. A questionnaire containing two sections and 17 variables in total were distributed among Medical Residents of different specialties except from ophthalmology residents. Participants of the study were selected through consecutive non probability sampling. Results: Mean hours of classroom based ophthalmology instruction during instruction during undergraduate program overall was 59.38 hours (55.9) and mean hours of clinical based ophthalmology instruction during undergraduate program overall was 62.73 hours (60.8) 54% were either not comfortable or somewhat comfortable in managing common ophthalmic condition. Conclusion: Teaching hours in under graduate program meet or exceed requisite criteria. However graduating doctors generally feel that the time spent does not provide them with the comfort and skill level required to care for patients with ocular presentations. Keywords: Ophthalmology, Ophthalmological conditions, Ophthalmological teaching, International Council of Ophthalmology Recommendations Background: Ophthalmological conditions are frequently encountered in almost all clinical specialties. Assessing the adequacy of ophthalmology teaching in undergraduate medical education is important in order to diagnose and manage different ophthalmological conditions. The objective of this study was to determine the comfort level of post graduate residents working in different clinical domains in managing common ophthalmic conditions. Methods: A cross sectional survey involving 277 post graduate residents was carried out over a period of six months in both private and public tertiary care hospital. A questionnaire containing two sections and 17 variables in total were distributed among Medical Residents of different specialties except ophthalmology residents. Participants of the study were selected through consecutive non probability sampling. Results: Mean hours of classroom based ophthalmology instruction during during undergraduate program was 59.38 hours (55.9) and mean hours of clinical based ophthalmology instruction during undergraduate program was 62.73 hours (60.8) 54% were either not comfortable or somewhat comfortable in managing common ophthalmic condition. Conclusion: Teaching hours in under graduate program meet or exceed requisite criteria. However graduating doctors generally feel that the time spent does not provide them with the comfort and skill level required to care for patients with ocular presentations. Keywords: Ophthalmology, Ophthalmological conditions, Ophthalmological teaching, International Council of Ophthalmology Recommendations